Copper-Mediated One-Pot Synthesis of Indoles through Sequential Hydroamination and Cross-Dehydrogenative Coupling Reaction - Sun, Peng; Yang, Jiaojiao; Song, Zirui; Cai, Yichao; Liu, Yajie; Chen, Chunxia; Chen, Xin; Peng, Jinsong (Synthesis, 2020)
Starting from simple anilines and ester arylpropiolates, an efficient one-pot synthesis of 2-arylindole-3-carboxylate derivatives has been developed through copper-mediated sequential hydroamination and cross-dehydrogenative coupling (CDC) reaction. The initial hydroamination of anilines to ester arylpropiolates in benzene can proceed in a stereoselective manner to give ester (Z)-3-(arylamino)acrylates in the presence of CuCl2/phenanthroline, KMnO4, and KHCO3 at 120 °C. Sequentially, these in situ functionalized adducts can undergo direct intramolecular oxidative alkenylation of aromatic C–H bond in mixed solvents (benzene/DMSO 1:1) at 130 °C affording multi-substituted indoles in good to high yields.
Keywords: copper-mediated; indoles; hydroamination; cross-dehydrogenative coupling; oxidation